2011
DOI: 10.3109/09553002.2011.573439
|View full text |Cite
|
Sign up to set email alerts
|

Effect of total body irradiation on late lung effects: Hidden dangers

Abstract: Purpose In our ongoing investigation into the consequences of a radiological terrorism event, we assessed whether a dose range that is believed to be subthreshold for the development of lung endpoints results in late pathological changes and, secondarily, whether those late changes affect the lung’s ability to respond to subsequent challenge. Materials and methods C57BL/6J mice received total body irradiation (0.5-10 Gy) and were followed for 6-18 months after irradiation. At 12 and 15 months, a subset of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…Previous studies from our lab have determined that lung exposure of C57BL/6J mice to irradiation results in dose-dependent increases in immune regulators, chemotactic proteins and inflammatory cytokines, such as IL-1, KC, and TNF-α, as well as repair factors such as collagen and TGF-β in the immediate days following exposure. Following a 12.5 Gy exposure, cyclical and time-dependent increases are also evident during the pneumonitic and fibrotic phases of the radiation response; while late changes in expression levels do not occur at late time points in mice exposed to lower radiation doses (0.5 Gy to 10 Gy) and are not associated with overt changes in pathophysiological endpoints (Johnston et al, 1995, Johnston et al, 1996, Johnston et al, 1998, Johnston et al, 2010, Johnston et al, 2011, Rubin et al, 1995, Manning et al, 2013). Furthermore, we have demonstrated that 12.5 Gy thoracic irradiation depletes resident pulmonary macrophages populations (Groves et al, 2015); their repopulation occurs in a subpopulation specific manner and with altered phenotypes from those originally contained within the lung (Groves et al, 2015, Hong et al, 2003).…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies from our lab have determined that lung exposure of C57BL/6J mice to irradiation results in dose-dependent increases in immune regulators, chemotactic proteins and inflammatory cytokines, such as IL-1, KC, and TNF-α, as well as repair factors such as collagen and TGF-β in the immediate days following exposure. Following a 12.5 Gy exposure, cyclical and time-dependent increases are also evident during the pneumonitic and fibrotic phases of the radiation response; while late changes in expression levels do not occur at late time points in mice exposed to lower radiation doses (0.5 Gy to 10 Gy) and are not associated with overt changes in pathophysiological endpoints (Johnston et al, 1995, Johnston et al, 1996, Johnston et al, 1998, Johnston et al, 2010, Johnston et al, 2011, Rubin et al, 1995, Manning et al, 2013). Furthermore, we have demonstrated that 12.5 Gy thoracic irradiation depletes resident pulmonary macrophages populations (Groves et al, 2015); their repopulation occurs in a subpopulation specific manner and with altered phenotypes from those originally contained within the lung (Groves et al, 2015, Hong et al, 2003).…”
Section: Discussionmentioning
confidence: 95%
“…Five days after arriving, mice were immobilized in customized plexiglass boxes or jigs and sham irradiated (control) or exposed to a single dose of gamma irradiation from a cesium-137 source. Customized jigs allowed irradiation of up to 10 mice for a total of 5 Gy TBI (without shielding, Figure 1(B)), eight mice for a total of 9 Gy sub-TBI (with shielding of the right hind leg, Figure 1(C)), or six mice for a total of 12.5 Gy TRI (local 30-mm diameter field and TBI with shielding of the head and abdomen/pelvis, Figure 1(D)) simultaneously at a dose rate of 98.41, 88.09, and 77.81 cGy/min, respectively (Figure 1(B-D)) (Travis et al 1980;Sharplin and Franko 1989;Rubin et al 1995;Johnston et al 1996Johnston et al , 2002Johnston et al , 2004Johnston et al , 2007Johnston et al , 2010Johnston et al , 2011Hong et al 2003;Down and Yanch 2010;Williams et al 2010). The dose uniformity was within approximately ±1.4% to 1.6% vertically.…”
Section: Animals and Treatmentmentioning
confidence: 99%
“…Previous studies from our group have shown that neonatal radiation exposure is associated with the production of pro-inflammatory molecules that have been implicated in the chronic inflammation and tissue remodeling associated with progression towards late radiation-induced pulmonary effects (22, 23). However, some investigators have proposed that these same pro-inflammatory molecules are protective in the context of the response to infection (2426), so may not necessarily play a role in the observed increased susceptibility to influenza.…”
Section: Resultsmentioning
confidence: 99%